2005
DOI: 10.1037/0002-9432.75.4.585
|View full text |Cite
|
Sign up to set email alerts
|

God forbid! Substance use among religious and nonreligious youth.

Abstract: Among a predominately Mexican and Mexican American sample of preadolescents, religiosity protected against lifetime alcohol, cigarette, and marijuana use and recent alcohol and cigarette use when religious affiliation was controlled. When religiosity was controlled, however, adolescents with no religious affiliation and adolescents who were religiously affiliated reported similar substance use outcomes. Interaction effects demonstrated that the protective effect of greater religiosity operated more strongly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
93
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 38 publications
8
93
2
3
Order By: Relevance
“…Research has consistently shown that more religiosity deters substance use (e.g., Marsiglia et al, 2005). The current study utilizes Bronfenbrenner's (1979) ecology of human development to conceptualize the interrelationships between religiosity, alcohol use attitudes, and alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has consistently shown that more religiosity deters substance use (e.g., Marsiglia et al, 2005). The current study utilizes Bronfenbrenner's (1979) ecology of human development to conceptualize the interrelationships between religiosity, alcohol use attitudes, and alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this may be that religion represents a salient aspect of African American culture (Hines & Boyd-Franklin, 2005). Religiosity has also been found to protect against substance use (Marsiglia et al, 2005;Walker, Ainette, Wills, & Mendoza, 2007;Wallace et al, 2003). Park and colleagues (2001) found that participation in religious activities predicted less alcohol use RELIGIOSITY AND ALCOHOL USE ATTITUDES…”
mentioning
confidence: 99%
“…Smoking is one of the most important health-compromising behaviors today (Sekulic and Tocilj 2006), while religiousness is found to be a protective factor against smoking in different ethnicities (Marsiglia et al 2005;Nonnemaker et al 2003;Francis and Mullen 1993). In previous studies performed on Serbian dancers of both genders, Sekulic et al (2009) found protective effects of religiousness against tobacco smoking, but in males exclusively.…”
Section: Religiousness In Relation To Cigarette Smoking and Appetite mentioning
confidence: 93%
“…A negative significant correlation between religiosity and drug abuse was reported in various studies. For instance, Gartnet et al (23) and Marsiglia et al (24) indicated that having religious tendencies and beliefs was associated with prevention and reduction of smoking and alcohol and drug abuse.…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, the results of the current study confirmed this correlation as well. This means that religious beliefs were associated with prevention and reduction of smoking and alcohol and drug abuse (23)(24)(25)(26)(27). Accordingly, it can be concluded that increasing social support, positive affection, and spirituality plays a significant role in enhancing teenagers' resilience to drug abuse.…”
mentioning
confidence: 99%